The Potency of Livestock Subsector Development in Banyumas Regency Central Java - Dharmawan, B; Suyono, Suyono (ANIMAL PRODUCTION, 2009)
Livestock subsector is one of source of economic growth on local or regional area. Therefore, government has to concern increasing the production intensity of livestock subsector. Banyumas Regency is one of region that has potency as center of livestock production in Central Java. The objectives of research were: (1) to know population target of livestock subsector superior commodity in Banyumas Regency for five years ahead; (2) to identify basis and no basis commodity; (3) to know the distribution of basis commodity; (4) to know area specialization of basis commodity; (5) to identify area growth in region; and (6) to know specialization of basis commodity in area. Result of research showed that: (1) the production increased on all livestock subsector for five years ahead and chicken had the biggest production level; (2) chicken was the biggest basis commodity in 17 subdistricts, then Sumpiuh and Kedungbanteng had the biggest amount of basis commodity, i.e. 6 basis commodities; (3) almost all basis commodity tend to spread randomly in several subdistrict especially chicken and goat; (4) every basis commodity in every subdistrict had positive coefficient specialization, thus, until now there were no subdistrict which specialized for certain commodity; (5) subdistricts that became basis commodity for chicken, sheep and goat were Lumbir, Jatilawang, Rawalo, Kebasen, Kemranjen, Tambak, Patikraja, Karanglewas, Kedungbanteng, and South Purwokerto; and (6) subdistricts that became basis commodity specialization of chicken, sheep and Goat were Lumbir, Jatilawang, Rawalo, Tambak, Patikraja and Kedungbanteng. (Animal Production 11(2): 71-78 (2009)Â Key Words: Banyumas, livestock subsector, basis commodity, forecasting method